Оцінювання траєкторії соціально-економічного розвитку України в умовах впливу зовнішніх шоків останнього десятиліття - Селюченко, Н. Є.; Seliuchenko, N. Y. (Видавництво Львівської політехніки, 2022)
Проаналізовано соціально-економічний розвиток України за 2012–2021 рр. з урахуванням десяти показників. На основі таксономічного показника рівня розвитку оцінено траєкторію соціально-економічного розвитку України та впорядковано за роками. Різниця між показниками таксономічного рівня розвитку (0,477) найкращого 2013 р. та найгіршого 2014 р. свідчить про майже стовідсоткове зниження інтегрального показника соціально-економічного розвитку внаслідок війни, а відхилення показника 2020 р. (0,312) також характеризує істотний негативний вплив пандемії Covid-19.

To assess the trajectory of the socio-economic development of Ukraine, a sample of ten indicators was formed for the period 2012–2021: nominal GDP of Ukraine; GDP per capita; direct foreign investment; index of industrial production; consumer price index; foreign trade balance; freight and passenger traffic; average monthly salary; salary arrears. In 2012–2013, the Ukrainian economy was still in a state of long-term recession after the global financial and economic crisis of 2008–2009. And already in 2014, there was a sharp deterioration of socio-economic indicators due to the annexation of Crimea and the resolution of the war in the Donetsk and Luhansk regions 2015–2019 are characterized by an improvement in the level of social and economic development of Ukraine. However, the Covid-19 pandemic has become another shock for the economy of Ukraine. Based on the formed sample, the taxonomic indicator of the level of development was calculated. According to the algorithm for calculating the taxonomic indicator of the level of development, all input indicators are divided into stimulators (high values increase the integral assessment) and destimulators (high values worsen the integral assessment). Among the indicators selected for the study, the consumer price index and salary arrears are classified as disincentives. All other indicators are stimulants. Standardized values of indicators were calculated on the basis of average values and standard deviations. Taking into account the taxonomic indicator of the level of development, the trajectory of the socio-economic development of Ukraine was evaluated and the years were ordered, in particular, the following ratings were assigned to them: 2013; 2019; 2018; 2017; 2021; 2012; 2016; 2020; 2015; 2014. The difference between the indicators of the taxonomic level of development of the best in the year 2013 and the worst in 2014 is 0.477 and indicates an almost one hundred percent decrease in the integral indicator of socio-economic development as a result of the war that began in the east of Ukraine in 2014. The deviation of the taxonomic level of development in 2020 from 2013 is equal to 0.312, which also characterizes the significant negative impact of the Covid-19 pandemic.
Assessment of the trajectory of socio-economic development of Ukraine in the conditions of the influence of external shocks of the last decade
Keywords: соціально-економічний розвиток; траєкторія; зовнішні шоки; війна; пандемія Covid-19; таксономічний показник рівня розвитку; ранжування; рейтинги; socio-economic development; trajectory; external shocks; war; the Covid-19 pandemic; taxonomic indicator of the level of development; ranking; ratings; 330.3